EDUKASI KEMANANAN PANGAN DAN GIZI BAGI KADER POSYANDU PADA MASA PANDEMI COVID-19 - Tria Astika Endah Permatasari; Hirfa Turrahmi; Illavina (Politeknik Negeri Sriwijaya, 2023)
During the Covid-19 pandemic, food processing that is halal, safe, and nutritious is necessary to increase immunity and maintain health. The purpose of this community service is to provide education on 'basil' (food safety and nutrition) which includes processing food that is halal, safe, healthy, and nutritious for posyandu cadres during the Covid-19 pandemic. The activity was carried out through a zoom meeting application for 30 posyandu cadres in Pasir Buncir Village in March-April 2021. The material provided covered the concept of halal, safe, healthy, and nutritious food processing. The success of the activity is measured using a pretest and posttest. Data were analyzed using the dependent t-test for the one-group pretest-posttest design. The results showed that there was a significant increase in the average knowledge score (p = 0.001) for posyandu cadres between the pre-test, namely 60.0 to 86.5 during the post-test. Food safety education programs need to be carried out in stages from posyandu cadres to pregnant women so that food safety and nutrition practices can be directly implemented in the food supply at the household level.